Inside Back Cover: A Heteroleptic Ferrous Complex with Mesoionic Bis(1, 2, 3‐triazol‐5‐ylidene) Ligands: Taming the MLCT Excited State of Iron(II) (Chem. Eur. J. 9/2015). Issue 9 (23rd February 2015) - Liu, Yizhu; Kjær, Kasper S.; Fredin, Lisa A.; Chábera, Pavel; Harlang, Tobias; Canton, Sophie E.; Lidin, Sven; Zhang, Jianxin; Lomoth, Reiner; Bergquist, Karl‐Erik; Persson, Petter; Wärnmark, Kenneth; et al.
<x xml:space="preserve">Abstract</x> A heteroleptic FeII complex combining benchmark 2, 2′‐bipyridine and strongly σ‐donating N‐heterocyclic carbene mesoionic ligands destabilizes the metal‐centered (MC) states relative to the metal‐to‐ligand charge transfer (3MLCT) state, resulting in a 13 ps 3MLCT lifetime. The potential energy surfaces show a deactivation pathway via the strongly singlet ground‐state (GS)‐coupled 3MC state instead of the typical FeII 5MC state, which is effectively removed from the excited state deactivation region, as reported by K. Wärnmark, V. Sundström et al. in their Full Paper on page 3628 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>